If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -55 + -12x = 35 + -9x Solving -55 + -12x = 35 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -55 + -12x + 9x = 35 + -9x + 9x Combine like terms: -12x + 9x = -3x -55 + -3x = 35 + -9x + 9x Combine like terms: -9x + 9x = 0 -55 + -3x = 35 + 0 -55 + -3x = 35 Add '55' to each side of the equation. -55 + 55 + -3x = 35 + 55 Combine like terms: -55 + 55 = 0 0 + -3x = 35 + 55 -3x = 35 + 55 Combine like terms: 35 + 55 = 90 -3x = 90 Divide each side by '-3'. x = -30 Simplifying x = -30
| -5(r+3)=-69 | | (x+5)(x+17)=0 | | 5x=4x+48 | | -16=n-12 | | -2x^2-2forx=3 | | -2(2m+7)=-28-6m | | 8b-5=68+23 | | -4x^2=45 | | -61+x=4x+23 | | -9=5x^2+x | | 1.8=6*x^2 | | H(t)=-16t^2+80t+6 | | 5x-8x-4=-4+3x | | x+3=-3x-1 | | 2(-9u+23)=100 | | 14x^2+9=14 | | 4x+3y=215000 | | a+15=33 | | 3x+5y=230000 | | 8(8y-52)=32 | | X+(-7)=(-12) | | 8x=3x+45 | | 4x-108=76+12x | | 3.3=7.8-0.5x | | 5.7n-4.7n+5.2=0.9 | | (4g+5)(g+1)=0 | | -10+x+-4-5=7x-5 | | x^2+12=14 | | 7(-3+31)=49 | | 12x-10=11x+11 | | 9-8x-4=-3x-13+x | | x*sqrt(x-1)=0 |